PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 019 BUMI AYU KECAMATAN DUMAI SELATAN - Julia Kartika Sari Julia Kartika Sari; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The research is the low learning of forth grade students of SDN 019 Bumi Ayu Kecamatan Dumai Selatan. Teacher usually using explained method. This method makes the students less passive and understanding. STAD cooperative learnig method can improve science learning of fourth grade students of SDN 019 Bumi Ayu Kecamatan Dumai Selatan academic year 2013/2014. This research was conducted in two cycles, the first cycle held two meetings, and the second cycle held two meetings. Data collection instrument in this research is teacher activity of observation sheet, students activity of observation sheet, and question sheet. This research is a class action research (PTK), the goals to improve science learning of forth grade students of SDN 019 Bumi Ayu Kecamatan Dumai Selatan in the subject changes of the physical environment. The result of the research is application of the STAD cooperative learning method to improve science learning of forth grade students of SDN 019 Bumi Ayu Kecamatan Dumai Selatan. In the first cycle assessment results is 80, and the second cycle is 87,8. The results of teacher activities in the first cycle of the first meeting is 58,33%, second meeting to 66,7%. In the second cycle of the first meeting 70,83%, and second meeting 83,33%, the results of students activities in the first cycle of the first meeting with an average 54,16%, second meeting to 62,5%, the second cycle of the first meeting to increased 75%, second meeting to increased 83,3%. This shows that application of STAD cooperative learning method can improve the results of scients learning of the forth grade students of SDN 019 Bumi Ayu Kecamatan Dumai Selatan. Key  words : cooperative model tipe STAD, Outcome learning IPA